Acute Myeloid Leukemia Epigenetic Immune Escape From Nature Killer Cells by ICAM-1 - Xiao, Yang; Chen, Jinghong; Wang, Jia; Guan, Wei; Wang, Mengzhen; Zhang, Linlin; Wang, Zhiding; Wang, Lixin; Yu, Li (Frontiers in Oncology, 2021)
Acute myeloid leukemia (AML), a malignant disorder of hemopoietic stem cells. AML can escape immunosurveillance of natural killer (NK) by gene mutation, fusions, and epigenetic modification, while the mechanism is not clearly understood. Here we show that the expression of Intercellular adhesion molecule‐1 (ICAM‐1, CD54) is silenced in AML cells. Decitabine could upregulate ICAM-1 expression, which contributes to the NK-AML cell conjugates and helps NK cells kill AML cells. We also show that ICAM-1 high expression can reverse the AML immune evasion and activate NK cells function in vivo. This study suggests that a combination of the hypomethylating agent and NK cell infusion could be a new strategy to cure AML.